Mirmecofauna em um fragmento de floresta atlântica urbana no município de Marília, SP, Brasil - Dáttilo, Wesley; Sibinel, Neiva [UNESP]; Falcão, Jéssica Caroline de Faria; Nunes, Rafael Vieira (My University, 2011)
The aim of this study was to verify the influence of the habitat fragmentation on the Ant Fauna in an urban fragment of Semideciduous Seasonal Atlantic Forest located in the municipality of Marília, São Paulo, Brazil. The studied fragment was divided into three environments in relation to edge: Edge (2m), Transition (30m) and Interior (90m). By using pitfalls traps and attractive baits there were done nine samples between November 2007 and February 2008. There were collected 3.873 individuals distributed into five subfamilies, 19 genera and 33 species. Five species were abundant on three studied environments: Ectatomma sp1, Mycocepurus goeldii, Paratrechina sp1, Pheidole sp2, Trachymyrmex sp1, Wasmannia auropunctata. The edge and transition environments presented the lower Simpsons diversity index and higher species dominance. However, it was observed little variation between these parameters between environments. Faunistic similarity between environments, expressed by Jaccard's similarity index showed high similarity between all studied environments. Because the studied site is an urban fragment, the similarity found between these areas can be related to habitat fragmentation process, an historical of constant anthropic perturbation and low local colonization rates. However, we suggest that a posteriori evaluation should be done with other arthropods groups like spiders and beetles in due to understand the changes that occur in urban fragments and support the choice of conservation and management actions in favor of this important forest remnant localized in urban area of Marília, São Paulo, Brazil.
Ant Fauna in a urban remnant of Atlantic Forest in the municipality of Marília, State Of São Paulo, Brazil
Keywords: Ants; Atlantic Forest; Bioindicators; São Paulo; Urban Fragmentation